The role of artificial intelligence in helping the blind achieve sustainable training in the arts (Al-Academy, 2026)
The current research aims to identify the role of Artificial Intelligence (AI) in assisting the Blind to achieve sustainable training in the arts. The significance of the research lies in highlighting the concept of AI as one of the most prominent contemporary technologies, its most important applications used in developing the skills of the Blind and clarifying the potential for achieving sustainable training in art practice for the Blind through AI applications. The research used the descriptive analytical methodology and reached several key findings, the most important of which are: AI applications specifically designed for the arts and aimed at the Blind provide the possibility of sustainable training in art practice without the need for continuous follow-up from supervisors or instructors. Furthermore, AI programs and applications for the Blind help develop their senses and enable them to utilize them, thereby contributing to the acquisition of various manual skills and their employment in their lives